2019
DOI: 10.1590/2236-8906-101/2018
|View full text |Cite
|
Sign up to set email alerts
|

Expandindo a distribuição geográfica de Hibiscus sabdariffa L. (Malvaceae): uma espécie naturalizada e negligenciada para a flora brasileira

Abstract: RESUMO Hibiscus sabdariffaé uma espécie pantropicalmente distribuída e cultivada devido à sua importância econômica. Possivelmente esta espécie é originária do Sudão, tendo sido, posteriormente, levada para o restante da África, sudeste da Ásia e América Central. Registros da naturalização de H. sabdariffa são conhecidos para a região neotropical, embora no Brasil, ela seja conhecida apenas como cultivada. Apresentamos aqui, casos de naturalização de H. sabdariffa para a flora brasileira baseados em registros … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…For floristic and phytosociological studies, it is only interesting to report the occurrence of exotic species merely cultivated to the site if they are clearly labeled in the study description (Moro et al, 2012) During field expeditions for this work, material from Hibiscus sabdariffa L. was collected from a disturbed area of secondary forest (Figure 3a-b). Coelho and Amorim (2019) found that this fact corresponds to an indication of naturalization of this species in the Brazilian Amazon.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…For floristic and phytosociological studies, it is only interesting to report the occurrence of exotic species merely cultivated to the site if they are clearly labeled in the study description (Moro et al, 2012) During field expeditions for this work, material from Hibiscus sabdariffa L. was collected from a disturbed area of secondary forest (Figure 3a-b). Coelho and Amorim (2019) found that this fact corresponds to an indication of naturalization of this species in the Brazilian Amazon.…”
Section: Resultsmentioning
confidence: 57%
“…Prior to the study by Coelho and Amorim (2019), Hibiscus sabdariffa was only recorded as cultivated (Esteves, Duarte & Takeuchi, 2014), being absent from the records of Brazilian angiosperms (BFG, 2015; Hibiscus in Flora do Brasil 2020, under construction). In this checklist, as in the study by Coelho and Amorim (2019), this species is labeled as naturalized and recorded as new occurrence for Brazil (Table 1). In addition to the new occurrences of exotic species, 39 new occurrences of native species were recorded for Amazonas State, eight of which are also new occurrences for the northern region (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O hibisco, Hibiscus sabdariffa L., também conhecido como vinagreira, azedinha, azeda-da-guiné, caruruazedo, chá-da-jamaica, quiabo-azedo ou rosélia, é considerada uma Planta Alimentícia Não Convencional (PANC), possivelmente originária do Sudão, e levada para o restante da África e Ásia (Coelho & Amorim, 2019). Os cálices carnosos e vermelhos nos frutos são utilizados para fins medicinais, pois possuem atividade antimicrobiana, diurética, anti-inflamatória, e atuam no tratamento da hipertensão (Mohamed et al, 2012).…”
Section: Flores De Hibisco (Hibiscus Sabdariffa L)unclassified
“…Moreover, although this crop is not considered of commercial importance in Brazil, it has favorable agronomic and biological characteristics for cultivation in the different Brazilian regions due to its high variability and rusticity (Kinupp & Lorenzi, 2014;Coelho & Amorim, 2019). The highest roselle consumption in Brazil occurs in the state of Maranhão, with the leaves of this species being used as the main ingredient of local traditional dishes, e.g., 'cuxá' and 'cuxá rice' (Cardoso, 1997).…”
Section: Introductionmentioning
confidence: 99%